The Mars Science Laboratory (MSL) Bagnold Dunes Campaign, Phase I: Overview and introduction to the special issue. Issue 1 (9th January 2018) - Bridges, Nathan T.; Ehlmann, Bethany L.
Abstract: The Bagnold dunes in Gale Crater, Mars, are the first active aeolian dune field explored in situ on another planet. The Curiosity rover visited the Bagnold dune field to understand modern winds, aeolian processes, rates, and structures; to determine dune material composition, provenance, and the extent and type of compositional sorting; and to collect knowledge that informs the interpretation of past aeolian processes that are preserved in the Martian sedimentary rock record. The Curiosity rover conducted a coordinated campaign of activities lasting 4 months, interspersed with other rover activities, and employing all of the rover's science instruments and several engineering capabilities. Described in 13 manuscripts and summarized here, the major findings of the Bagnold Dunes Campaign, Phase I, include the following: the characterization of and explanation for a distinctive, meter‐scale size of sinuous aeolian bedform formed in the high kinetic viscosity regime of Mars' thin atmosphere; articulation and evaluation of a grain splash model that successfully explains the occurrence of saltation even at wind speeds below the fluid threshold; determination of the dune sands' basaltic mineralogy and crystal chemistry in comparison with other soils and sedimentary rocks; and characterization of chemically distinctive volatile reservoirs in sand‐sized versus dust‐sized fractions of Mars soil, including two volatile‐bearing types of amorphous phases. Plain Language Summary: Over the course of several months, the Curiosity rover explored the Bagnold dune field in Gale crater, Mars. This was the first time a robotic space mission had visited active, migrating sand dunes on the surface of another planet. In overall dune shape, sand grain size, and dune in migration in the direction of the strongest winds, Curiosity found that dunes on Mars were similar in many ways to those on Earth. But there were also discoveries of key differences that indicate how wind‐related processes work. A distinctive type of ripple observed at the Bagnold dunes—sinuous and larger than typical for Earth—may form from conditions specific to Mars' very thin atmosphere. Also, modeling results show that a few grains making short hops cause a large cascade of grain hops ‐‐ and thus dune migration ‐‐ even at very low wind speeds, a characteristic unique to Mars' low gravity. Unlike what is typical for Earth, the Martian sand grains have different compositions depending on size. Also, the sand dunes are free of the relatively ubiquitous Mars dust, probably due to ongoing wind activity blowing the dust away in suspension. By comparing the chemistries of the dust‐free dune sands with more typical sandy‐dusty soils, Curiosity discovered elevated sulfur, chlorine, and water in the soils that was easily released by heating. Thus, exploration of the Bagnold dunes revealed many important processes shaping the modern Mars landscape and the chemistry of materials on the Mars surface. Key Points: Curiosity's Bagnold Dunes Campaign, Phase I, was the first in situ exploration of an active extraterrestrial dune field Wind speed, morphology, grain size, mineralogy, and chemistry were measured over 4 months, interspersed with other rover activities Key findings include meter‐scale bedforms, saltation at low wind speeds, and particle‐size‐dependent chemistry, mineralogy, and volatile reservoirs in Martian fines